Kompetensi, Persepsi, dan Motivasi Mahasiswa Manajemen Zakat IAIN Kudus terhadap Minat menjadi Amil Zakat (Institut Agama Islam Negeri Kudus, 2025)
Abstract With the increasing demand for quality graduates from higher education, students are required not only to possess academic degrees but also to possess professional competencies relevant to the needs of the workplace. In this context, career development in zakat management has become a strategic option, particularly for graduates of the Zakat and Waqf Management study program. This study aims to examine the influence of the competencies, perceptions, and motivations of Zakat and Waqf Management students at IAIN Kudus on their interest in becoming amil zakat (alms collectors). The research method used was a quantitative survey approach. The population was IAIN Kudus Zakat and Waqf Management students, and the sample consisted of 43 respondents from the 2021 batch of Zakat and Waqf Management students. A questionnaire was used for data collection. The data were analyzed using SPSS analysis tools and multiple linear regression analysis. The conclusion from the research is that student competencies and perceptions do not affect interest in becoming an amil zakat, while student motivation has a positive and significant effect. Keywords: Competence; Perception; Motivation; Interest; Amil Zakat. Abstrak Seiring dengan meningkatnya tuntutan kualitas lulusan pendidikan tinggi, mahasiswa tidak hanya dituntut memiliki gelar akademik, tetapi juga kompetensi profesional yang relevan dengan kebutuhan dunia kerja. Dalam konteks ini, pengembangan karier di bidang pengelolaan zakat menjadi salah satu pilihan strategis, khususnya bagi lulusan program studi Manajemen Zakat dan Wakaf. Penelitian ini bertujuan guna menguji pengaruh kompetensi, persepsi, dan motivasi mahasiswa manajemen zakat dan wakaf IAIN Kudus terhadap minat menjadi amil zakat. Jenis penelitian yang dipergunakan yakni kuantitatif berpendekatan survei. Populasi pada penelitian ini yakni mahasiswa Manajemen Zakat dan Wakaf IAIN Kudus dan sampel penelitian yang digunakan yaitu mahasiswa manajemen zakat dan wakaf IAIN Kudus Angkatan 2021 sejumlah 43 responden. Kuesioner digunakan dalam proses pengumpulan data. Data hasil penelitian dianalisis menggunakan alat analisis SPSS dengan menggunakan analisis regresi linier berganda. Kesimpulan dari hasil penelitian yang sudah dilakukan yaitu kompetensi dan persepsi mahasiswa tidak berpengaruh terhadap minat menjadi amil zakat, sedangkan motivasi mahasiswa berpengaruh positif dan signifikan terhadap minat menjadi amil. Kata Kunci: Kompetensi; Persepsi; Motivasi; Minat; Amil Zakat.